Design and Analysis of the Gear Conjugate Profile based on the Sine- curved Benchmark Tooth Profile - Cui Gaoshang; Fan Yuanxun (Jixie chuandong)
The benchmark tooth profile of gear cutter is designed to a sine curve. The gear conjugate profile is solved by tooth profile normal method. The meshing line,curvature and relative sliding ratio are analyzed,and then the bending strength is analyzed through the finite element analysis software ANSYS. The results show that the meshing line is similar to a splay,and the value of curvature and relative sliding ratio is small compared to the involute spur gear pair,and the maximum bending stress occurs in the dedendum which is smaller than the involute gear maximum bending stress.